Sex-differences in relation to the association between patterns of physical activity and sedentary behavior with frailty. (March 2020) - Kehler, D. Scott; Clara, Ian; Hiebert, Brett; Stammers, Andrew N.; Hay, Jacqueline L.; Schultz, Annette; Arora, Rakesh C.; Tangri, Navdeep; Duhamel, Todd A.
Highlights: Higher amounts of sporadic and bouts of MVPA related to lower frailty in both sexes Prolonged sedentary bouts were associated with higher frailty in women but not men Duration and intensity of breaking up sedentary time lowered frailty in both sexes Abstract: Objective: To investigate the sex-difference in relation to the association between moderate-vigorous physical activity (MVPA) and sedentary time (ST) patterns with frailty. Method: Accelerometry from ≥50 year olds from the National Health and Nutrition Examination Survey (2003-04/2005-06 cycles) were included. Bouted and sporadic MVPA were defined as MVPA in ≥10 min or <10 min durations, respectively. MVPA was analyzed based on meeting 0 %, 1–49 %, 50–99 %, and ≥100 % of the physical activity guidelines of 150 min/week. A duration of ≥30 minutes defined prolonged ST. The frequency (≥1 min interruption in ST), intensity and duration of breaks from ST were calculated. A 46-item frailty index (FI) quantified frailty. Multivariable linear regression models adjusted for demographics, total sedentary time, and accelerometer wear time. Results: There were 1143 females and 1174 males available for analysis. Bouted MVPA was associated with lower frailty levels; the association peaked at meeting 50–99 % of the guidelines in females and ≥1.0 % in males (p = NS for sex-interaction). Meeting a higher proportion of the guidelines through sporadic MVPA was significantly associated with a lower FI in males only (p = NS for sex-interaction). Prolonged ST bouts were associated with worse frailty in females but not males (p < 0.05 sex-interaction). Average break intensity was associated with a lower FI in both sexes, whereas, total sedentary breaks were not (p = NS for sex-interaction). Average break duration was associated with frailty in males (p = NS for sex-interaction). Conclusion: Prolonged ST was more detrimentally associated with frailty in females than males, which could influence tailored movement prescriptions and guidelines.